Relative contributions of strength, anthropometric, and body composition characteristics to estimated propulsive force in young male swimmers - Cochrane, K. C.; Housh, T. J.; Smith, C. M.; Hill, E. C.; Jenkins, N. D. M.; Johnson, G. O.; Housh, D. J.; Schmidt, R. J.; Cramer, J. T. (The Journal of Strength and Conditioning Research, 2015)
The purpose of this study was to determine the relative contributions of isokinetic forearm flexion (FLX) and extension (EXT) peak torque (PT) at 180°/s, height (HT), percent body fat (%BF), and fat-free mass (FFM) to the prediction of estimated propulsive force (EPF) and which of these variables should be a focus of training in young male swimmers. Thirty young male swimmers (mean age ± SD = 12.4 ± 2.7 years) volunteered for this study. The subjects were members of local swimming clubs who competed in the front crawl. The swimmers were measured for FLX and EXT PT at 180°/s, HT, body mass (BM), arm muscle area (AMA), arm circumference, triceps skinfold, %BF, and FFM. Arm muscle area was used to calculate EPF. Zero-order correlations and stepwise multiple regression analyses were used to examine the relationships among variables and the relative contributions of FLX, EXT, HT, %BF, and FFM to the prediction of EPF. Forearm flexion PT at 180°/s, EXT, BM, HT, FFM, AMA, and EPF were significantly intercorrelated (r = 0.83-1.00). In addition, 4 variables contributed significantly to the prediction of EPF (standardized regression coefficients = FFM [1.00], FLX [0.92], EXT [-0.62], and HT [-0.35]). Percent body fat did not contribute to any of the stepwise models. These findings suggested that age-related increases in HT and FFM, as well as training for increases in FLX and EXT strength may improve propulsive force and swimming performance in young male swimmers.